The Effect Of Short Intermittent Training And Medium Intermittent Training On Maximal Aerobic Speed Mas For Senior Handball Players - Boussadia, Yakoub; Kharoubi, Mohamed Fayçal; Sefir , Hadj (sports creativity, 2025)
The study aimed to know the impact of the short intermittent training (IT) (10”-20”) and medium IT (15”- 45”) on the maximal aerobic speed (MAS) for senior handball players, the research sample consisted of two experimental groups each group contain 8 players, who were selected deliberately and using the experimental method and as tools for the study was used the physical tests (Yo-Yo intermittent test). The data were statistically processed by SPSS, the results indicated that the effect of short IT bigger than the medium IT on maximum aerobic speed MAS and for senior handball players.